Post-O-level studies in modern languages - Russell, C. V. (Commonwealth and international library. Language division., 1970)
Post-O-level Studies in Modern Languages is a 14-chapter book that begins with an explanation of the changing structure of the sixth-form curriculum and the outlining of a model curriculum based on five areas of experience: communication; sociological and cultural aspects; mathematics; scientific education; and aesthetic experience.